Phase formation in the Ni-enriched zone below the surface oxide on NiTi. (March 2023) - Freiberg, K.E.; Seyring, M.; Wonneberger, R.; Rettenmayr, M.; Undisz, A.
Abstract: Upon exposure to oxygen, NiTi forms a Ti-rich surface oxide layer, and mass balance requires that a Ni-enriched zone forms below the oxide. Both the surface oxide layer and the Ni-enriched zone are discussed to affect key properties of NiTi as material for minimally invasive medical application or for actuators, e.g., the release of Ni and the resistance to initiation and propagation of cracks when exploiting the shape memory effect/pseudoelasticity. However, owing to the small extension of the Ni-enriched zone of a few nanometers, little is known about its crystallinity, phase and evolution of composition. We study the formation of the surface layers during annealing at ∼500 °C for up to 10 min, as routinely applied for shape-setting. With an approach employing nano beam electron diffraction in a transmission electron microscope and an in-house software package for phase analysis it is shown for the first time that phase transformations in the Ni-enriched zone, specifically from NiTi to Ni4 Ti3, occur already after 2 min of annealing, much earlier than documented in the literature. Furthermore, the phase transformation to the thermodynamically stable Ni3 Ti in the Ni-enriched zone is shown to be mediated by metastable Ni4 Ti3 . In contrast to Ni4 Ti3 precipitates in NiTi bulk, the morphology of the crystalline phases is granular. Considering the swift formation of Ni-rich phases below the surface oxide and the observation of a band-like diffraction contrast in the TEM images originating from crystal interfaces, a phase transformation mechanism in the Ni-enriched zone is suggested consisting of short range order rearrangements of atoms. Highlights: Phase formation in the Ni-enriched zone is characterized in detail using TEM. Ni-rich phases form unexpectedly fast, already after annealing for 2 min at ∼500 °C. The transformation to thermodynamically stable Ni3 Ti is mediated by metastable Ni4 Ti3 . Short range order rearrangement of atoms is proposed, enabling prompt transformation. Effect of Ni-rich phases should be considered carefully for application of NiTi.